Unpacking teachers' personal accomplishments within the JD-R model: The roles of leadership, communication, and collaboration - Alanoglu, Muslim; Vural, Gursen; Uslukaya, Alper; Turan, Cihat; Demirtas, Zulfu (Sage Publications Ltd, 2026)
This study examines how principals' learning-centered leadership behaviors, communication skills, and promotion of teacher collaboration are associated with teachers' sense of personal accomplishment, as framed by the Job Demands-Resources (JD-R) model. Data were collected via an online survey from 2723 teachers across 12 geographical regions of T & uuml;rkiye during the 2024-2025 academic year. Structural equation modelling revealed that learning-centered leadership was positively related to teachers' sense of personal accomplishment, both directly and indirectly through collaboration with teachers. Furthermore, principals' communication skills were found to be a significant moderator, indicating that higher communication competence is associated with a stronger relationship between leadership and collaboration. Moderated mediation analysis further indicated that high communication competence is associated with a stronger indirect relationship between leadership and personal accomplishment through collaboration in the model. These findings imply that leadership-driven job resources may play an especially influential role in centralized education systems, where teachers' autonomy is limited, by highlighting how communication is associated with collaborative practices and psychological resilience. By contextualizing the JD-R model within T & uuml;rkiye's hierarchical governance structure, this study expands the model's cultural applicability and offers practical insights for leadership development policies that aim to reinforce collaborative and supportive school environments.
Keywords: School leadership; teacher collaboration; personal accomplishment; communication skills